Mulheres, poder e direitos fundamentais: uma análise da perspectiva das empresas privadas no Brasil - Padilha , Renata Ferrari (2023)
In the last decades, there has been a considerable evolution in women's access to public spaces; they are more present in politics, in the economy, and in the labor market. This expansion movement of women's participation in society, especially in public spaces, is the result and fruit of the historical struggles observed from the feminist waves, which sought not only equal conditions between men and women, but the recognition of rights capable of truly ensuring gender equality. When evaluating the clipping related to the labor market it is possible to observe that, even though the female worker's profile has evolved - they are more qualified and more active - it is still possible to observe gender inequality that prevents them from reaching their effective emancipation. The presence of women in top leadership positions and strategic management is still considerably lower than that of men, which denotes a scenario of exclusion of women from decision-making positions. In this sense, considering the analytical category of the control of the bodies, structured by Michel Foucault, we intended to investigate whether it is possible to affirm that the exclusion of women from top leadership and strategic management positions, and consequently from power, represents a violation of the Fundamental Rights of women, especially that of gender equity, to the extent that it reproduces the exclusion of women from the public and decision-making positions. In the same way, we intended to investigate whether women who have effectively reached leadership positions in the private sector perceive the recurrence of signs representative of the characterization of the sexual division of labor in the daily life of companies. It was assumed that women occupy fewer leadership positions, and those who reach such positions are still relegated to service management positions, thus reproducing aspects of the sexual division of labor, which assigns to women the internal and less prestigious activities and to men the more relevant functions of decision making and, consequently, of power control. Thus, the objectives of the study were to understand how the power mechanisms studied by Foucault works, especially regarding the biopower focused on the control of the collective body, the disciplines and methods used to docilize the bodies, questioning the way this control permeates the female body; to identify, from the different waves of feminism, the path women have taken for their inclusion in the public domain, considering the positivization of these rights; identify the place that women effectively occupy in the private business environment and whether this place reproduces the sexual division of labor; and, identify whether there is a perception by women of the signs that show the characterization of the sexual division of labor in the daily life of companies, through qualitative research. As a theoretical base, we used the Foucault´s theory of power, to observe how the mechanisms of control of the bodies work in the business environment, the feminist theory related to power, violence, and gender by Heleieth Saffioti, as well as the theorization involving the sexual division of labor by Helena Hirata and Daniéle Kergoat, correlating such concepts to the phenomenon of female exclusion. The methodological option that allowed us to evaluate the exclusion of women from positions of high leadership and strategic management in the private sector and, furthermore, how these controls permeate the entire business fabric is discourse analysis, to not only investigate how the discourse is organized through a system of rules and constitutive elements, but also, to understand the force and effects through which it imposes itself in the private business environment. The data analysis allowed us to conclude that there is a persistence and reproduction in the labor market of historically and socially constructed roles that attribute to women the responsibility for service, internal, and less prestigious activities. This construction is reflected in the low representation of women in leadership positions, and in the exclusion of women in strategic management, decision-making, and power positions, reinforcing the stratification of the continuity of male control of power